Population Corner: Advancing Digital-Based Literacy Through The School Literacy Movement at SMA Negeri 1 Stabat - Salmayda, Salmayda; Utomo, Dwiyono Hari; Mutia, Tuti; Handoyo, Budi; Suharto, Yusuf (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2024)
This study examines the Population Corner initiative at SMA Negeri 1 Stabat, intending to improve digital literacy through the School Literacy Movement (SLM). The main objectives are to provide an overview of the Population Corner program at SMA Negeri 1 Stabat as a form of digital-based SLM implementation and to assess students' literacy levels in population content using a qualitative approach to guide the development of a more effective Population Corner. The results showed that although the initiative has successfully integrated digital tools such as QR codes and cloud-based platforms to improve access to information, many students are not actively using these resources. Limitations of this study include the absence of structured management and a dedicated space for the Population Corner, which may affect its effectiveness. In addition, the study highlighted that many students were not fully engaged with the program, indicating the need for better strategies to encourage interest in population literacy activities. Recommendations for future improvements include increasing student engagement through dynamic activities, integrating interdisciplinary connections, providing geospatial resources, and improving the school's digital infrastructure to improve access to resources. Addressing these limitations and implementing the recommended strategies, the Population Corner initiative can increase literacy and awareness of critical population issues at the local and national levels.